Platformisation of Education: An Analysis of South African Universities’ Learning Management Systems - Kazeem Ajasa Badaru; Emmanuel O. Adu (Research in Social Sciences and Technology- OpenED Network, 2022)
Several studies have focused attention on the crisis of the COVID-19 pandemic and the impact on the traditional face-to-face teaching and learning activities across the globe. There is, however, little research regarding the platformisation of education with the aid of the learning management systems (LMSs) in the contexts of South African universities. With a thematic content analysis of the extant literature and a systematic review of universities’ websites, this study explored and unearthed various LMS platforms which public universities in South Africa adopted and utilized before the outbreak of the COVID-19 pandemic and during the lockdown period. The findings revealed that the majority (46%) of South Africa’s public universities used the Blackboard LMS while another 34 percent of the 26 universities used the Moodle LMS. The rest of the public universities in South Africa used one of the following LMS platforms: the Vula, Efundi, ClickUp, RUConnected, Sakai, SunLearn, Canvas, and D2LBrightspace. Furthermore, the study found that a few South African universities had moved from one LMS platform to another, especially during the period of lockdown precipitated by the pandemic; beginning from the year 2020. The LMS platforms serve the pedagogical needs of the universities in terms of facilitation of online interaction between instructors and students, dissemination of course materials, announcements, submissions, assessments, and grading of student assignments electronically. It is recommended that future studies should investigate the challenging factors responsible for the switch from one LMS platform to another across the public universities in South Africa.